PERBANDINGAN STRATEGI PEMBELAJARAN TIPE STAD (STUDENT TEAMS ACHIEVEMENT) DAN STRATEGI PEMBELAJARAN TIPE TGT (TEAM-GAMES-TOURNAMENT) TERHADAP HASIL BELAJAR PKn MATERI POKOK DEMOKRASI PANCASILA DI KELAS X SMA NEGERI 1 BATANGONANG - RISWANDI HARAHAP (Institut Pendidikan Tapanuli Selatan, 2018)
The study aims to look at the difference between the Comparison Results Learning Civics Topic Pancasila Democracy Kooperatife Learning Model Using Type STAD With Learning Model Kooperatipe TGT Type Class X SMA Negeri 1 Batangonang. The population number of 258 people. Sample of 64 people. The collected data were analyzed with descriptive analysis used t-test test The research study Pancasila democracy Civics subject matter using type STAD cooperative learning model has an average value of 57.59 in the category of